Implementation of the Jigsaw Type Cooperative Model Using Pop Up Book Media to Increase Elementary School Students' Mathematics Learning Activeness - Saputri, Nofa Qomara Ika; Wulandari, Bunga Ayu; Indryani, Indryani (Jurnal Simki Pedagogia, 2024)
The aim of this research is to find out how to apply the Jigsaw Type Cooperative learning model in increasing student activity in elementary school mathematics learning. The research method used is a classroom action research method that uses the development model by Kemmis and Mc. Taggart. The subjects of this research were 32 class VI students at SD Negeri 207/IV Jambi City. Data was collected using observation techniques, questionnaires and written tests. Data analysis uses quantitative descriptive analysis. The results of the research prove that the application of the jigsaw cooperative learning model can increase the learning activity of class VI students in the mathematics subject of plane figures. The average results of observing students' learning activity in cycle I was 87.52%, in cycle II it increased to 90.00%, the results of the student learning activity questionnaire obtained an average in cycle I of 60.55% and in cycle II it increased to 89.31%.